An analysis of Politeness Strategies Used by Major Characters in Social Game : A study of Seventh Singularity Story of Fate/Grand Order Social Game: A study of Seventh Singularity Story of Fate/Grand Order Social Game - Lina Tri Astuty Beru Sembiring; Eli Diana; Zesy Aditya (English Education Study Program Faculty of Teacher Training and Education, 2022)
Politeness strategy is used in conversations to save addressee’s face by performing an expression that is less threatening for the addressee’s face. The aims of this research are to analyze politeness strategies used by two major characters of the seventh singularity story of Fate/Grand Order social game, and also to analyze the factors that influencing their choicess of politeness strategies. This research employed a descriptive qualitative method. The description of the data is in the form of utterances and examined based on Brown and Levinson theories of politeness strategy. Based on the obtained result, it can be concluded that the two major characters, Mash Kyrielight and Enkidu/Kingu applied four kinds of politeness strategy (bald on record, positive politeness, negative politeness and off record). Both characters mainly used positive politeness strategy, while the least used strategy is bald on-record. Their choice of politeness strategies mostly influenced by social distance factor, imposition and also the power factor.